2015
DOI: 10.1075/ihll.5.10val
|View full text |Cite
|
Sign up to set email alerts
|

Eventive and stative passives and copula selection in Canadian and American Heritage Speaker Spanish

Abstract: Spanish captures the difference between eventive and stative passives via an obligatory choice between two copula; verbal passives take the copula ser and adjectival passives take the copula estar. In this study, we compare and contrast US and Canadian heritage speakers of Spanish on their knowledge of this difference in relation to copula choice in Spanish. The backgrounds of the target groups differ significantly from each other in that only one of them, the Canadian group, has grown up in a societal multili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…This difference was significant. Thus, consistent with previous studies (Bruhn de Garavito and Valenzuela 2008;Valenzuela et al 2015), L2 learners and HL learners found the verbal passive with era less acceptable than verbal passives with fue.…”
Section: Gjtsupporting
confidence: 92%
See 3 more Smart Citations
“…This difference was significant. Thus, consistent with previous studies (Bruhn de Garavito and Valenzuela 2008;Valenzuela et al 2015), L2 learners and HL learners found the verbal passive with era less acceptable than verbal passives with fue.…”
Section: Gjtsupporting
confidence: 92%
“…Our results may provide clues for why in previous studies (Valenzuela et al 2015;Bruhn de Garavito and Valenzuela 2008), L2 and HL learners showed low acceptability ratings for the verbal passive with era. Learners' misinterpretation of this structure may be rooted in a grammar that has yet to incorporate the verbal passive with the copula ser in the imperfect.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Results of resting-state connectivity analysis for model 1Canada versus the United States (see ref 65…”
mentioning
confidence: 99%